Information on wheat cultivars recommended for sowing in Rio Grande do Sul in 1991 - C. S. Moreira, João; N. A. de Sousa, Cantídio; P. Gomes, Edar; C. Medeiros, Milton (Pesquisa Agropecuaria Brasileira, 1998)
The success of the wheat crop depends on the integral use of the technological factors recommended for the crop. Among them the choice of the cultivar to be sown becomes of great importance. Having in minf the great number of materials recommended in Rio Grande do Sul (RS), which show differences in relation to the cycle, height, reaction to diseases and other characteristics, the choice of one of them is a complex task, mainly in function of the climatic conditions, which are much variable over different years. An evaluation of the yield data from the wheat state cultivar trial (Ensaio Estadual de Cultivares de Trigo) was carried out considering many places from 1986 to 1990 with the objective of helping in the choice of the most adequate cultivar for every wheat region in RS. The study was conducted with the material recommended for sowing in this area, aiming at making available to wheat producers, in addition to yield data, information allowing the farmer to choose, with great safety, the germplasm that over the years has shown better performance in each region or in the State. In this way only two cultivars, in all nine wheat regions in RS, BR 32 and BR 34, were always superior to the check CEP 14-Tapes, one of the germplasms most planted during the evaluation period, considering the performance of the cultivar under recommendation.